Assessing the Acceptability, Feasibility and Sustainability of an Intervention to Increase Detection of Domestic Violence and Abuse in Patients Suffering From Severe Mental Illness: A Qualitative Study - Ruijne, Roos E.; Kamperman, Astrid M.; Trevillion, Kylee; Garofalo, Carlo; van der Gaag, Mark; Zarchev, Milan; Bogaerts, Stefan; Howard, Louise M.; Mulder, Cornelis L. (Frontiers in Psychiatry, 2020)
Rationale: Despite interventions to improve detection rates, domestic violence and abuse (DVA) remains largely undetected by healthcare services. We therefore aimed to examine the acceptability, feasibility and sustainability of an intervention aiming to improve DVA detection rates, which included a clear referral pathway(i.e., the BRAVE intervention) and to explore the acceptability and feasibility of DVA management and referrals in general, in the context of low detection rates. Methods: Qualitative study design with four focus groups of 16 community mental health (CMH) clinicians from both control and intervention arms. The focus groups discussed managing DVA in clinical practice and staff experiences with the BRAVE intervention in particular. Focus groups continued until saturation of the subject was reached. Interviews were analyzed using a thematic analysis approach. Results: DVA was seen to be highly relevant to mental healthcare but is also a very sensitive subject. Barriers in CMH professionals, institutions and society meant CMH professionals often refrained from asking about DVA in patients. Barriers included communication difficulties between CMH professionals and DVA professionals , a fear of disrupting the therapeutic alliance with the patient, and a lack of appropriate services to help victims of DVA. Conclusion: The BRAVE intervention was acceptable but not feasible or sustainable. Personal, institutional and public barriers make it not feasible for CMH professionals to detect DVA in mental healthcare. To increase the detection of DVA, professional standards should be combined with training, feedback sessions with peers and DVA counselors, and routine enquiry about DVA. Trial registration: ISRCTN register number: ISRCTN14115257